A Clinical Study of Pharyngolaryngectomy with Total Esophagectomy: Postoperative Complications, Countermeasures, and Prognoses. (September 2015) - Kamiyama, Ryosuke; Mitani, Hiroki; Yonekawa, Hiroyuki; Fukushima, Hirofumi; Sasaki, Toru; Shimbashi, Wataru; Seto, Akira; Koizumi, Yuh; Ebina, Aya; Kawabata, Kazuyoshi
Objective: Patients with advanced hypopharyngeal or cervical esophageal cancer have a comparatively high risk of also developing thoracic esophageal cancer. Pharyngolaryngectomy with total esophagectomy is highly invasive, and few reports about it exist. We examined the postoperative complications and respective countermeasures and prognoses of patients who underwent pharyngolaryngectomy with total esophagectomy. Study Design: Case series with chart review. Setting: Department of Head and Neck Oncology, Cancer Institute Hospital of Japanese Foundation for Cancer Research, Japan. Subjects and Methods: We examined the postoperative complications and respective countermeasures and prognoses of 40 patients who underwent pharyngolaryngectomy with total esophagectomy in our hospital. Results: Postoperative complications were observed in 23 patients (57.5%) and consisted of 8 groups: tracheal region necrosis in 5 patients; neck abscess formation/wound infection in 5; fistula in 4; tracheostomy suture leakage in 2; ileus in 2; lymphorrhea in 2; pulmonary complications in 2; and other complications, including hemothorax, tracheoinnominate artery fistula, temporary cardiac arrest due to intraoperative mediastinum operation, methicillin-resistant Staphylococcus aureus enteritis, and sepsis, in 1 patient each. A lethal complication—brachiocephalic vein hemorrhage due to tracheostomy suture leakage and hemorrhagic shock due to tracheoinnominate artery fistula—occurred in 2 (5%) patients. The crude 5-year survival rate was 48.6%. Conclusions: Serious postoperative complications were related to tracheostomaplasty. Although pharyngolaryngectomy with total esophagectomy is highly invasive, we believe that our outlined treatment method is the most appropriate for cases of advanced hypopharyngeal or cervical esophageal cancer that also requires concurrent surgery for esophageal cancer.